PENGARUH E-COMMERCE DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI DALAM PENGAMBILAN KEPUTUSAN UNTUK BERWIRAUSAHA DI ITC CIPULIR SELAMA MASA PANDEMIC COVID19 - Adhani, Ida; Istiqomah, Istiqomah (Accounting Research and Business Journal, 2023)
This study aims to determine the effect of e-commerce and the use of accounting information systems in making decisions for entrepreneurship at ITC Cipulir during the covid19 pandemic. The selected sample is 60 respondents who use a survey method with a questionnaire technique. The analytical technique used in this research is Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination and Hypothesis Testing. The results of data analysis show that the results of partial hypothesis testing of e-commerce (X1) and the use of accounting information systems (X2) affect entrepreneurial decision making (Y) based on the results of the study indicate that e-commerce and accounting information systems have a significant positive effect on entrepreneurial decision making.